Urban poverty in China - Wu, Fulong; Webster, Chris; He, Shenjing; Liu, Yuting (Edward Elgar, 2010)
"Urban poverty is an emerging problem. This book explores the household and neighbourhood factors that lead to both the generation and continuance of urban poverty in China. It is argued that the urban Chinese are not a homogenous social group, but combine laid-off workers and rural migrants, resulting in stark contrasts between migrant and workers' neighbourhoods and villages." "The expert authors examine the new urban poor in China and the dynamics of their poor neighbourhoods, highlighting both household experience and neighbourhood changes affecting the urban poor. Urban Poverty in China is based upon a comprehensive household survey in six Chinese cities and provides insights into microscopic and neighbourhood-level poverty dynamics. The comprehensive study explores the spatial implications such as concentration of poverty as well as the differentiation within poor neighbourhoods." "This informative book tells an insightful story about evolving urban poverty in Chinese cities that will be invaluable to researchers and postgraduate students within urban studies, geography, social policy and development studies as well as Chinese and Asian studies. It will also prove to be an invaluable read for researchers in urban and social development and international development agencies."--BOOK JACKET.